A Corpus-Based Comparison of the Pragmatic Use of Qian and Hou to Examine the Applicability of Space–Time Metaphor Hypothesis in Early Child Mandarin - Tsung, Linda; Wu, Dandan (Frontiers in Psychology, 2021)
The Universal Space-Time Mapping Hypothesis suggests that temporal expression is based on spatial metaphor for all human beings. This study examines its applicability in the Chinese language using the data elicited from the Early Childhood Mandarin Corpus (ECMC) (Li & Tse, 2011), which collected the utterances produced by 168 Mandarin-speaking preschoolers in a semi-structured play context. The unique pair of Chinese words, qian (前/before/front) and hou (后/after/back), which can be used to express either time (before/after) or space (front/back) in daily communication, was the unit of analysis. The results indicated that: (1) there was a significant age effect in the production of ‘qian/hou,' indicating that the period before the age of 4.5 may be critical for the development of temporal and spatial expression; (2) the pair was produced to express time (before/after) much earlier than space (front/back), indicating that the expression of time might not necessarily be based on the spatial metaphor; and (3) the pair was used more frequently to express time (before/after) than space (front/back) by the preschoolers, thus challenging the Hypothesis.